Aproximações sobre arquitetura paraguaia contemporânea - Lopes, Eduardo Verri (2016)
This dissertation analyzes part of the contemporary Paraguayan architecture, designed by a group of professionals who converge on common concepts: the understanding of the socioeconomic context, the architecture's adequacy to the place and the role of structural and constructive systems in the spatial configuration. The work was developed through exploratory research, interviews, technical visits, literature review and access to the architect's archives. We initiate the research with the background of this production, from the 1930s to the present day, approaching the foreign architectural influences and the role played by Solano Benítez and Javier Corvalán as binders of the group. We seek to identify, by reading nine residential projects built between 2005and 2012, and interviews with the architects, the elements that unite the professionals in the group ,which is reiterated by the participation in Taller E - FADA/UNA and in Colectivo Aqua Alta. By linking work and discourse, the research registers the coherency revealed in the architectural production that establishes a School.